A Structural Functional Model for Managing the Digital Potential of a Strategic Innovatively Active Industrial Cluster - Babkin, A.; Tashenova, L.; Mamrayeva, D.; Andreeva, T. (International Journal of Technology, 2021)
The age of digital transformation produced by industrial enterprises shifting to new forms of production and actively using versatile information and communications technologies has made issues with the management of digital potential especially vital. These trends have prompted the formation of integrated intellectual structures, called strategic innovatively active industrial clusters, whose primary unique feature is that they operate on a single digital platform. The purpose of this study is the construction of a structural-functional model for managing the digital potential of a strategic innovatively active industrial cluster to use for creating a methodology to assess this potential. The research methods include analysis and synthesis as well as graphic interpretation and content analysis. The main results of this study are as follows: a structural-functional model has been developed for use in managing the digital potential of a strategic innovatively active industrial cluster that harmoniously reflects the roles of all the subsystems forming the cluster, and a methodology has also been developed based on the created model to help measure the digital potential of a cluster, using one such cluster in the city of St. Petersburg, Russia as an example. The novelty of this study is in its development of a model that fully and comprehensively reflects the special features of managing the digital potential of newly integrated structures such as strategic innovatively active industrial clusters. In addition, the practical significance of the obtained results is that they can be used to calculate the real current values of the digital potential of these clusters and assist in the making of relevant management decisions for operational and strategic planning.
Keywords: digital potential; Industrial cluster; Management model; Methodology to assess the digital potential; Single digital platform; Strategic innovatively active industrial cluster